Much ado about nothing? Smoking bans and Germany's hospitality industry - Michael Kvasnicka; Harald Tauchmann (Applied Economics, 2012)
Over the past years, public smoking bans have been introduced in most European countries. Unlike elsewhere, in Germany such bans were introduced at state level at different points in time, which provides important intra-country regional variation that can be exploited to identify the effects of such bans on the hospitality industry. Using monthly data from a compulsory survey carried out by the German Federal Statistical Office, we study the short-run effects that these bans had on establishments' sales. In contrast to the largely US-based literature, we find that smoke-free policies had a negative (yet moderate) effect on establishment sales. Closure rates of businesses in the hospitality industry, however, were not significantly affected by the introduction of state smoking bans.
Keywords: 330; smoking bans; sales; intra-country regional variation